A prevalent caveolin-1 gene rs926198 variant is associated with type 2 diabetes mellitus in the Thai population - Metha Yaikwawong; Pornpimon Ek-eudomsuk; Gunya Sittithumcharee; Vipavee Anupunpisit; Thavatchai Peerapatdit; Chaicharn Deerochanawong; Thep Himathongkam; Siwanon Jirawatnotai; Somlak Chuengsamarn (Scientific Reports)
Abstract This study investigated the associations between CAV1 variants and metabolic syndrome (MetS), type 2 diabetes mellitus (T2DM), and cardiometabolic risk factors, as well as the influence of CAV1 variants on CAV1 mRNA expression. We genotyped 743 T2DM patients for CAV1 variants. Multiple logistic regression was conducted to adjust for sex, age, and body mass index (BMI), and odds ratios (ORs) with 95% confidence intervals (CIs) were calculated. The expression of mRNA was measured by reverse transcription polymerase chain reaction. The rs926198 variant, but not the rs3807989 variant, was associated with T2DM. Crude ORs were 1.87 (95% CI: 1.32–2.69, p = 0.0005) and adjusted ORs were 1.81 (95% CI: 1.12–2.96, p = 0.016), respectively. Additionally, patients with Mets and T2DM who had the rs926198 variant exhibited a significant 44.3% reduction in CAV1 mRNA expression (P < 0.05). Clinical samples revealed that the rs926198 variant is strongly linked to T2DM, with significantly reduced CAV1 mRNA. Our findings suggest a crucial role for the rs926198 variant in T2DM, indicating its potential for prevention, diagnosis, and intervention purposes.